Regulatory Basis for Counteracting Corruption and Confiscation of Illegally Acquired Property - Nedyalkova, Elena (Law Journal of New Bulgarian University, 2024)
The article examines the emergence and development of the Bulgarian legislation governing the fight against corruption and the legal institute for confiscation of illegally acquired property in favor of the state. The subject of analysis are the strategic goals of the current legislation, the establishment of illegally acquired property, the concepts and measures for countering corruption.